Detection of intermolecular transferred‐NOE interactions in small and medium size protein complexes: RANTES complexed with a CCR5 N‐terminal peptide. (24th January 2017) - Abayev, Meital; Srivastava, Gautam; Arshava, Boris; Naider, Fred; Anglister, Jacob
Abstract : NMR is a powerful tool for studying structural details of protein/peptide complexes exhibiting weak to medium binding ( K D > 10 μm ). However, it has been assumed that intermolecular nuclear Overhauser effect (NOE) interactions are difficult to observe in such complexes. We demonstrate that intermolecular NOEs can be revealed by combining the 13 C‐edited/ 13 C‐filtered experiment with the transferred NOE effect (TRNOE). Due to the TRNOE phenomenon, intermolecular NOE cross peaks are characterized by both the chemical shifts (CSs) of the protein protons and the average CSs of the peptide protons, which are dominated by the CSs of the protons of the free peptide. Previously, the TRNOE phenomenon was used almost exclusively to investigate the conformation of small ligands bound to large biomolecules. Here, we demonstrate that TRNOE can be extended to enable the study of intermolecular interactions in small‐ and medium‐sized protein complexes. We used the 13 C‐edited/ 13 C‐filtered TRNOE experiment to study the interactions of the chemokine regulated upon activation, normal T cell, expressed and secreted (RANTES) with a 27‐residue peptide, containing two sulfotyrosine residues, representing the N‐terminal segment of the CCR5 receptor ((Nt‐CCR5(1–27). The TRNOE phenomenon led to more than doubling of the signal‐to‐noise ratios (SNRs) for the intermolecular NOEs observed in the 13 C‐edited/ 13 C‐filtered experiment for the 11.5‐kDa monomeric RANTES/Nt‐CCR5(1–27) complex. An even better improvement in the SNR was achieved with dimeric Nt‐CCR5(1–27)/RANTES (23 kDa), especially in comparison with the spectra measured with a 1 : 1 protein to peptide ratio. In principle, the isotope‐edited/isotope‐filtered TRNOE spectrum can discern all intermolecular interactions involving nonexchangeable protons in the complex. Abstract : It is challenging to obtain intermolecular NOEs for small‐ and medium‐sized protein complexes exhibiting weak binding and fast off‐rates. We demonstrate that intermolecular NOEs can be detected by combining 13 C‐edited/ 13 C‐filtered experiments with the transferred NOE effect (TRNOE). The TRNOE phenomenon enhances the signal‐to‐noises for the intermolecular NOEs, enabling detection of signals that are otherwise obscured.